Hydrated proton complexes supplementation for tumor microenvironment reprogramming: a bioenergetic strategy targeting the Warburg effect and mitochondrial dysfunction - Edgar, Alfred Lee; Lopes, Luis Felipe Dias; Lopes, Eduarda Grando; Felin, Izabella Danezi; Felin, Carlos Roberto; Gaspary, João Francisco Pollo (Frontiers in Oncology, 2025)
BackgroundThe tumor microenvironment (TME) is characterized by a reversed pH gradient—acidic extracellular and alkaline intracellular conditions—arising from mitochondrial dysfunction, metabolic reprogramming, and dysregulated proton transport. These alterations establish a permissive niche for tumor progression, immune evasion, and resistance to therapy. Although the TME is increasingly recognized as a key determinant of cancer behavior, effective and targeted strategies for its bioenergetic reprogramming remain scarce.ObjectivesThis study introduces and evaluates Eigen/Zundel Complexes-Rich Water (EZC-Rich Water) as a novel hydrated proton supplementation strategy capable of targeting Warburg-induced proton dysregulation and restoring mitochondrial function, while stabilizing electrochemical membrane dynamics within the TME.MethodsA structured translational research design was implemented, combining Work Breakdown Structure (WBS), Open Innovation, and Design Thinking methodologies. This approach enabled the identification of Fundamental Points of View (FPV’s)—physiological targets underlying TME dysfunction—and Critical Success Factors (CSF’s)—mechanistic requirements for therapeutic efficacy. Multicriteria decision analysis was applied to integrate findings from oncology, bioenergetics, and physical chemistry, linking hydrated proton supplementation to improved zeta potential, electrosmotic flow, mitochondrial coupling, and redox regulation.ResultsIntegrative analyses demonstrated that EZC-Rich Water delivers metastable hydrated proton clusters (H9O4+ and H5O2+) that support selective and efficient proton transfer via the Grotthuss mechanism. This supplementation facilitates compartmentalized acid–base modulation without inducing systemic acidosis, aligning with prioritized FPV’s and validated CSF’s. The proposed strategy shows translational potential to correct pH inversion, optimize oxidative phosphorylation, and restore bioenergetic integrity in the TME.ConclusionHydrated proton supplementation through EZC-Rich Water represents an innovative bioenergetic intervention with potential to reprogram the tumor microenvironment. By targeting core metabolic dysfunctions such as the Warburg effect and mitochondrial uncoupling, this clinically adaptable and low-risk strategy introduces a new paradigm in nutritional oncology. Further preclinical and clinical studies are warranted to validate its efficacy, safety, and translational applicability in oncology and related metabolic disorders.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?, identifier CRD420251065137; https://www.crd.york.ac.uk/prospero/display_record.php?, identifier CRD420251022205.